Heightened noise sensitivity as a predictor of psychological prognosis in older adults with traumatic brain injury - Liu, Huili; Li, Jingzhou (Frontiers in Psychiatry, 2025)
BackgroundOlder adults are prone to falls, which may lead to traumatic brain injury, and the resulting psychological problems are also quite prominent. The purpose of this study is to explore the predictive role of recent noise hypersensitivity after mild traumatic brain injury (mTBI) in the risk of psychological problems such as depression and anxiety in the medium and long term.MethodsA total of 1,003 older adults (60 years old or older) with mTBI were included. At the short-term (2 weeks), medium-term (3 months), and long-term (12 months) after injury, the Rivermead Post-Concussion Symptoms Questionnaire, Hamilton Depression Scale, and Hamilton Anxiety Scale were used to assess patients’ noise hypersensitivity, depression, and anxiety symptoms, respectively. According to the short-term noise hypersensitivity, all patients were divided into the noise-sensitive group (n=441) and the non-sensitive group (n=592), and multivariate logistic regression was used to evaluate the association of noise hypersensitivity with depression and anxiety.ResultsShort-term noise hypersensitivity after injury was correlated with medium-term and long-term depressive symptoms after injury (OR=1.063, 95%CI=1.027~1.100, P=0.001; OR=1.039, 95%CI=1.016~1.063, P=0.001), but not with short-term depressive symptoms after injury (OR=1.027, 95%CI=0.980~1.076, P=0.259). Short-term noise hypersensitivity was correlated with medium-term and long-term anxiety symptoms (OR=1.048, 95%CI=1.015~1.083, P=0.004; OR=1.042, 95%CI=1.013~1.073, P=0.004), but not with short-term anxiety symptoms (OR=1.034, 95%CI=0.991~1.078, P=0.128).ConclusionEarly-stage noise hypersensitivity after mTBI in older adults links to higher risk of mid- and late-stage adverse psychological prognosis (depression or anxiety). Whether noise hypersensitivity can predict post-injury psychological status in this population requires further verification.